Serum Creatinine as a Potential Biomarker of Skeletal Muscle Atrophy in Non-small Cell Lung Cancer Patients - das Neves, Willian; Alves, Christiano R. R.; de Souza Borges, Ana Paula; de Castro, Gilberto (Frontiers in Physiology, 2021)
Objectives: Identifying simple biomarkers to determine muscle atrophy in non-small-cell lung cancer (NSCLC) patients remains a critical research gap. Since creatinine is mainly a product from intramuscular creatine metabolism, we tested the hypothesis that low serum creatinine levels would be associated to skeletal muscle atrophy in NSCLC patients. Materials and Methods: This is a prospective cohort study including 106 treatment-naive patients with histologically confirmed stage IV NSCLC. All patients performed routine serum creatinine laboratory tests. We divided patients into two groups based on low (< 0.7 mg/dL for male and < 0.5 mg/dL for female) or normal creatinine levels. We compared body mass index (BMI), psoas muscle cross-sectional area, adipose tissue area and complete blood counts between groups. Results: Male and female NSCLC patients with low serum creatinine levels had low muscle cross-sectional area as compared to patients with normal serum creatinine levels. Male NSCLC patients with low serum creatinine also displayed reduced BMI, reduced adipose tissue area, and elevated systemic inflammation compared to NSCLC patients with normal serum creatinine levels. There were no significant differences between female groups for BMI, adipose tissue area and inflammatory markers. Conclusions: Serum creatinine is a potential prognostic biomarker of skeletal muscle atrophy in NSCLC patients. Since serum creatinine is a simple and accessible measurement, we suggest that it should be monitored in longitudinal follow-up of NSCLC patients as a biomarker of muscle atrophy.